2018
DOI: 10.3390/ijms19010313
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Frizzled Receptors in Hepatocellular Carcinoma

Abstract: G protein-coupled receptors (GPCRs) have a substantial role in tumorigenesis and are described as a “cancer driver”. Aberrant expression or activation of GPCRs leads to the deregulation of downstream signaling pathways, thereby promoting cancer progression. In hepatocellular carcinoma (HCC), the Wnt signaling pathway is frequently activated and it is associated with an aggressive HCC phenotype. Frizzled (FZD) receptors, a family member of GPCRs, are known to mediate Wnt signaling. Accumulating findings have re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 98 publications
2
15
0
Order By: Relevance
“…6D), in agreement with earlier studies linking Wnt receptor (FZD7) overexpression to Wnt pathway activation in HBV-related HCC (37). Interestingly, treatment of HBV replicating DDX5 KD cells with sorafenib reduced expression of genes which act as negative effectors of Wnt activation (38), specifically Secreted Frizzled Related Protein 4 (SFRP4) and SFRP5 (Fig. 6D).…”
Section: Transcriptomic Analyses Define Dysregulated Wnt Signaling Insupporting
confidence: 91%
See 1 more Smart Citation
“…6D), in agreement with earlier studies linking Wnt receptor (FZD7) overexpression to Wnt pathway activation in HBV-related HCC (37). Interestingly, treatment of HBV replicating DDX5 KD cells with sorafenib reduced expression of genes which act as negative effectors of Wnt activation (38), specifically Secreted Frizzled Related Protein 4 (SFRP4) and SFRP5 (Fig. 6D).…”
Section: Transcriptomic Analyses Define Dysregulated Wnt Signaling Insupporting
confidence: 91%
“…Interestingly, our results also show that sorafenib treatment of HBV replicating DDX5 KD cells suppressed expression of the negative Wnt effectors SFRP4 and SFRP5, while increasing expression of DVL1 and DVL3 ( Fig. 7) which prevent β-catenin degradation (38). Collectively, our observations support that downregulation of DDX5 is a clinically relevant player in the pathogenesis of poor prognosis HBV-associated HCCs.…”
Section: Discussionsupporting
confidence: 76%
“…With the exception of FZD5, other FZDs, including FZD3, FZD4, FZD8, and especially FZD9, can also significantly promote LRP5/␤-catenin signaling in a ligand-independent manner. Because ectopic expression of FZDs in tumor cells is a common phenomenon (34,35), these findings may provide an alternative mechanism to comprehensively understand the molecular basis underlying tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…6H), implying that the endogenous canonical WNT glycoproteins were not involved in suppressing GSK3␤-AXIN-APC complexes. Therefore, we concluded that ectopic expression of Frizzled receptors (34,35), such as FZD3/4/5/9, which cause ligand-independent LRP5/6 signalosome activation, might be the putative pathological factor for the constitutive activation of WNT/␤-catenin signaling in HepG2 cells.…”
Section: Ligand-independent Fzd-lrp5/6 Signaling May Be Involved In Tmentioning
confidence: 92%
“…Overactivation of the WNT pathway is associated with a number of human malignancies, including (but not limited to) cancers of lungs, ovaries, breast, skin, brain and intestinal tract (Clevers and Nusse, 2012). In some subsets of these cancers, different FZD receptors are overexpressed, leading to an amplification of the WNT signal (Chan and Lo, 2018;Ueno et al, 2013). Importantly, pan-WNT inhibitory therapies cause toxic side effects, due to the importance of WNT signaling in other tissues, such as the maintenance of the intestinal epithelium (Korinek et al, 1998;Schepers and Clevers, 2012;van Es et al, 2012).…”
Section: Wnt-fzd Co-receptors In Regenerative Medicine and Cancermentioning
confidence: 99%